Lokalne skupnosti in skupnostna skrb na področju duševnega zdravja - Zupančič, Vesna (Družboslovne razprave, 2014)
The contribution highlights the local community's role in community care development in the area of mental health as seen by three participating groups: municipal officials (local community/administrative entity officials), providers within the network of mental health programmes and services, and users of these services. A cross-sectional case study was carried out in the Novo mesto health region using a combination of quantitative and qualitative methods aimed at evaluating the current state of care and establishing whether differences are present in the understanding of local communities' role in community mental health care development. The findings of the study indicate opportunities for improving community care processes.
Keywords: Duševno zdravje; Mental health; Socialno skrbstvo; Community care; Local communities; Lokalne skupnosti